DAYA TARIK WISATA EVENT PACU JALUR DESA SETAKO RAYA KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Lestari, Dyah Wahyuni; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Attraction is one of the things that can attract tourists to visit tourist event locations. A tourist object must meet development requirements in the form of something to see, something to do, something to buy, something to arrived and something to stay in order to attract tourists. This study aims to determine the tourist attraction of the Pacu jalur event in Setako Raya Village and to find out the obstacles and efforts made by the manager of the Pacu jalur event in Setako Raya Village, Peranap District, Indragiri Hulu Regency. Researchers used research methods in the form of observation, interviews and documentation. The results of this study can be concluded that Setako Raya Village fulfills the five development requirements in the form of something to see, something to do, something to buy, something to arrived, and also something to stay. However, the implementation of these five conditions has not been fully optimal and sufficient for tourists. Keywords: Attraction, Event, Pacu Jalur, Setako Raya Village